Associations of multiple toxic metal exposures with metabolic dysfunction-associated fatty liver disease: NHANES 2011–2018 - Li, Yuguang; Liu, Zefeng; Chang, Yu; Chen, Naifei; Zhang, Rong; Liu, Xiangliang; Song, Wei; Lu, Jin (Frontiers in Nutrition, 2023)
Background: The occurrence of metabolic dysfunction-associated fatty liver disease (MASLD) is driven by multiple factors including obesity, hypertension, dyslipidemia, and insulin resistance.However, epidemiological research investigating the association between metal exposure and MASLD occurrence remains limited.Methods: We conducted a large cross-sectional study with 6520 participants who were involved in the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2018. Using generalized linear regression, we examined the relationship between five heavy metals (mercury, manganese, lead, selenium, cadmium) and MASLD. Furthermore, restricted cubic spline models and weighted quantile sum (WQS) analysis were employed to characterize the exposure-response relationship between the five metals and MASLD.Results: Higher blood selenium levels were associated with an increased likelihood of MASLD among US adults. Blood lead exposure was also positively correlated with MASLD risk. However, there was no significant association observed between blood cadmium, mercury, manganese levels, and MASLD risk. Among the five metals, blood cadmium exposure accounted for the highest proportion of MASLD risk. Conclusion: Our study indicated the significant association between blood cadmium and lead exposure levels and the occurrence of MASLD in a representative sample of US adults.